Management of Organic Manure and Inorganic Fertilizer in The Maize-Mungbean/Dhaincha-T. Aman Rice Cropping Pattern for Increased Crop Production - Rahman, MH; Islam, MR; Jahiruddin, M; Haque, MQ (Bangladesh Journal of Agricultural Research, 2012)
The study was conducted at the On Farm Research Division (OFRD) farm, Rangpur from 2002-2003 to 2004-2005 to see the effect of inorganic fertilizers along with organic manure and mungbean residue on soil properties and yield of crops. For the first crop (maize), there were five treatments. After harvest of maize, mungbean and dhaincha (Sesbania) seeds were sown as per treatments. For T. Aman rice (third crop), each of the treatments (T2 and T3 plots) were subdivided into six, so there were altogether 15 treatments. Integrated use of manure and inorganic fertilizers (IPNS basis) produced comparable seed yield of maize with the chemical fertilizers alone irrespective of moderate or high yield goal basis (MYG or HYG). The highest maize yield of 10.02 t/ha was obtained from the treatment T5, which produced significantly highest yield over all other treatments. During the growing period of mungbean, temperature coupled with rainfall encouraged vegetative growth of mungbean and as a result, pod formation was low. The incorporation of Sesbania biomass and mungbean residue along with inorganic fertilizers for MYG produced identical grain yields of T.Aman rice with the fertilizers alone for HYG. The highest grain yield 4.31 t/ha was found in IPNS dhaincha along with fertilizers for HYG treatment. There was no remarkable change in post harvest soil status during the growing period. It may be concluded that addition of mungbean residues or Sesbania biomass before T. Aman rice may ensure higher crop productivity and sustain soil fertility. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11224 Bangladesh J. Agril. Res. 37(2): 225-234, June 2012